A case study on the high employee turnover rate of MPH bookstores at mid Valley Megamall / Syarifah ‘Atikah Wafa Syed Mohd. Ghazali Wafa - Syed Mohd. Ghazali Wafa, Syarifah ‘Atikah Wafa (2010)
This case study is undertaken so as to identify what are the factors that influence high employee turnover rate of MPH Bookstores at Mid Valley Megamall branch. From the study undertaken, after gathering information from both primary and secondary data, the reasons for this issue to arise are because of employment of students and part-timers as staff and also because of better job offer by other companies and rivals. Apart from that, it is also to have a better understanding regarding what are the practices the company has taken in order to prevent this issue and to come out with recommendations that can help the company to reduce the rate. Some of the practices taken are by rewarding staffs and also through Key Performance Indicators (KPI). From the factors and practices, analysis has been made and recommendations are made in hope that it can help the company to reduce its high employee turnover rate in future.